INFLUENCE OF ORGANIC AND INORGANIC NUTRIENT SOURCES ON THE PROXIMATE COMPOSITION OF SELECTED MALVACEAE VEGETABLES - Elumalero G. O.; Akinbile, O.O.; Amujoyegbe B. J.; Odeniran A.F.; Ogunbela, A. A.; Apenah M. O.; Samuel, A.M.; Akinremi, T.I. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The experiment was carried out at Obafemi Awolowo University Teaching and Research farm located at longitude 4’33o E and latitude 7’28° N, 224 meters above sea level, laid out in a split block design with three replicates including the organic, inorganic (NPK 20:10:10) and control plot. Crude fibre (5.92%) and Ether (3.79%) content of the organic fertilizer were significantly different from the NPK 20:10:10 (5.27%; 4.17%) and control (4.53%; 3.97%). NPK 20:10:10 significantly influenced Ether content (4.17%) when compared to organic fertilizer (3.79%) and control (3.97%). The influence of the nutrient sources differs for each vegetable, ranging from the crude fibre, crude protein and ether content, which were the nutritional quality parameters assessed.